Memaknai Laba Bagi Petani dan Tengkulak Garam Madura - Nasifa; Emilia Sula, Atik (Jurnal Penelitian Ekonomi Akuntansi, 2024)
This study aims to determine the differences in the meaning of profit for Madura salt farmers and middlemen. The location of the research was Pangarengan District, Sampang Regency. This research uses a qualitative approach. Informants in this study are a number of salt farmers who manage their own land and salt middlemen in Pengarengan sub-district, where both parties have experienced in the field of salt production and distribution for more than two years. Data analysis in this study uses systematic data analysis with several steps, namely data reduction, data presentation and conclusion drawing. The results showed that the meaning of profit for farmers and middlemen is not much different, namely getting as much profit as possible but has different purposes of use. According to salt farmers, profit is used to fulfill daily needs and pay debts, while according to middlemen, profit is used to develop business and improve economic standards